A Survey: Big Data Ethics and Challenges in Healthcare Division - Madhu, HK; BR, Prakash (International Journal of Computer Sciences and Engineering, 2025)
The era of automation, robotics, Internet of Things and collaborative networked systems generated an uniquely characterized data which is named as Big data due to the presence of sensor, camera and text generators poses challenges of storage, processing, and analysis. In this paper, the advanced health care system of future is discussed which generates the Big data along with the conventional methods of data analytics on medical Big data its trends, limitations and further research possibilities. In this paper, a general characteristic of Bigdata is discussed then a thorough study on the future healthcare process and management will be described. Then discuss how the data generated in the context of the Healthcare system will have big data characteristics. Finally, collect all the state of artwork for medical big data analytics and discuss the research gap and open issues.